Global Nonexistence for a System of Nonlinear Viscoelastic Wave Equations - Quispe Méndez, Teófanes (2017)
We consider a mixed problem for a system of nonlinear viscoelastic wave equations. We prove the existence of its local solution by the Faedo-Galerkin method and show the blow-up of solutions by the indirect method.